A new model for service and application convergence in B3G - Munoz, M. (IEEE Wireless communications)
4G mobile communication networks encompass heterogeneous technologies that can be categorized at different levels according to their access coverage. Personal area, body area, and ad hoc networks are defined at a personal level, WLAN and UWB are examples at a local/ home level, and 3G technologies such as UMTS are technologies at a cellular level. In spite of their heterogeneity, these technologies shall be seamlessly integrated in 4G networks, naturally creating an open architecture. By openness we mean that the network architecture is divided into different layers, and the communication between these layers is performed through open interfaces or APIs. Although this open integration between 4G technologies is normally presented at the lower layers (connectivity and control), integration at the upper layers (service and application) is equally important. In this article we present a new model for service and application integration in 4G networks. This model generalizes the different service and application creation environments defined for each of the previously mentioned technologies, providing a uniform and interoperable framework for 4G services and applications. The model is based on a hierarchical architecture that provides compatibility for services in different technologies and at the same time is able to capture the specific details for each particular technology. The model also defines how 4G applications should be specified. In the last part of this article we present a testbed we have implemented in order to validate this model.